2022
DOI: 10.3390/children9050627
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Caring for Children with Genetic or Rare Diseases: A Mixed-Methods Study

Abstract: As a factor in parenting stress, gender differences in caring for children with genetic or rare diseases warrant research attention; therefore, this study explored gender differences in parenting stress, health outcomes, and illness perceptions among caregivers of pediatric genetic or rare disease populations to improve the understanding of such gender differences. Applying a concurrent triangulation mixed-methods design, we conducted a questionnaire survey to assess study measures for 100 family caregivers (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Obviously, this affects the perception of caregivers toward the quality of life of children affected by RDs. Although the data we used in the educational subscale are limited, they corroborate the study of Chu et al [40] regarding the fact that the perceived dimensions of a disease differ as a function of the type of condition. In this sense, the diseases with greater statistical significance are Ehlers-Danlos Syndrome (systemic disease), congenital limb deficiency (embryogenic disease) and spina bifida (neurological and embryogenic disease).…”
Section: Perception Of the Quality Of Life Related To Educationsupporting
confidence: 84%
See 2 more Smart Citations
“…Obviously, this affects the perception of caregivers toward the quality of life of children affected by RDs. Although the data we used in the educational subscale are limited, they corroborate the study of Chu et al [40] regarding the fact that the perceived dimensions of a disease differ as a function of the type of condition. In this sense, the diseases with greater statistical significance are Ehlers-Danlos Syndrome (systemic disease), congenital limb deficiency (embryogenic disease) and spina bifida (neurological and embryogenic disease).…”
Section: Perception Of the Quality Of Life Related To Educationsupporting
confidence: 84%
“…In our case, the meta-regression by informant did not reveal significant data with respect to the mothers. Nevertheless, studies such as that of Chu et al [40] concluded that, while female caregivers perceive the diseases of their children as highly symptomatic, along with a greater need for biosanitary control of the pathology, male caregivers show more negative perceptions with respect to the general quality of life of the minors. In addition, most of the informants were mothers or female caregivers, which can influence the attainment of greater scores in the perception of the quality of life of minors with RDs [17,21,22,36,41].…”
Section: Perception Of the Quality Of Social Lifementioning
confidence: 99%
See 1 more Smart Citation
“…In a mixed-methods study, Chu and colleagues [ 5 ] explored gender differences in parenting stress, health outcomes, and illness perceptions among 100 family caregivers (42 men and 58 women) caring for children with genetic or rare diseases in Taiwan. Measures included the Pediatric Inventory for Parents (PIP) to assess caregiver distress, the Center for Epidemiological Studies Depression Scale Short Form (CES-D Sort Form) to assess caregiver depression, and the Satisfaction with Life Scale (SWLS) to assess life satisfaction [ 5 ]. Open-ended questions were theoretically informed, using Leventhal’s Common-Sense Model of Illness Representation.…”
Section: Contributions To the Special Issuementioning
confidence: 99%
“…The financial burden of caregiving for a child is further complexified by the fact that sex and gender are major determinants of the caregiving experience. 20 , 35 , 41 , 42 The concept of sex, referring to a set of biological attributes assigned at birth, is often interchangeably used with the concept of gender, which refers to sociocultural characteristics evolving in time. 42 Indeed, not only are females more likely than males (sex) to be informal caregivers, gendered characteristics traditionally ascribed with femininity have also been shown to increase the burden.…”
Section: Introductionmentioning
confidence: 99%